2017
DOI: 10.1080/1359432x.2017.1314265
|View full text |Cite
|
Sign up to set email alerts
|

Identifying long-term patterns of work-related rumination: associations with job demands and well-being outcomes

Abstract: The aim of this 2-year longitudinal study was to identify long-term patterns of work-related rumination in terms of affective rumination, problem-solving pondering, and lack of psychological detachment from work during off-job time. We also examined how the patterns differed in job demands and wellbeing outcomes. The data were collected via questionnaires in three waves among employees (N = 664). Through latent profile analysis (LPA), five stable long-term patterns of rumination were identified: (1) no ruminat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
78
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 55 publications
6
78
1
Order By: Relevance
“…The questionnaire data were collected in three waves using electronic questionnaires (see Kinnunen et al, 2017). First, in spring 2013 (Time 1), of the employees contacted (N = 3,593), 1,347 returned the completed questionnaire after two reminders, yielding a response rate of 36%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The questionnaire data were collected in three waves using electronic questionnaires (see Kinnunen et al, 2017). First, in spring 2013 (Time 1), of the employees contacted (N = 3,593), 1,347 returned the completed questionnaire after two reminders, yielding a response rate of 36%.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, in a cross‐sectional study by Querstret and Cropley () affective rumination was significantly associated with increased work‐related fatigue. It has also been shown that those scoring high in affective rumination showed least work engagement, of which vigour is a part, over a 2‐year period (Kinnunen et al ., ). Based on this evidence, we hypothesize the following:…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…There is some evidence showing that perseverative cognitions are key mediators in the unfavourable relations between job demands and sleep (De Witte, Pienaar, & De Cuyper, ; Van Laethem et al ., ). Moreover, challenge (e.g., workload, cognitive demands) and hindrance (e.g., job insecurity) demands have previously been related to high affective rumination, lower psychological detachment from work during off‐job time, and greater need for recovery (Höge, Sora, Weber, Peiró, & Caballer, ; Kinnunen, Mauno, & Siltaloppi, ; Kinnunen et al ., ). A recent meta‐analysis has shown that especially challenge demands relate to poor detachment from work during off‐job time (Bennett, Bakker, & Field, ), which may refer to affective rumination.…”
Section: Introductionmentioning
confidence: 99%